2022
DOI: 10.1111/wvn.12577
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pre‐exposure prophylaxis (PrEP) program for HIV prevention in a federally qualified health center (FQHC)

Abstract: Background Preventing new cases of the human immunodeficiency virus (HIV) is key to the Centers for Disease Control and Prevention (CDC) Ending the HIV Epidemic: A Plan for America initiative. In 2012, Truvada became the first medication approved in the United States to prevent HIV infection, yet it has not seen widespread use. Aim This study aimed to allow for the incorporation of an HIV risk assessment into the primary care provider (PCP) visit and promote increased numbers of patients screened for pre‐expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In addition, regular and repeated teaching on PrEP, such as the educational lecture we provided during this intervention, is needed for all clinicians because many did not have this education in their formal training. A previous study that tested an intervention to improve PrEP uptake at a FHQC found they were able to increase PrEP prescriptions using education and an electronic HIV risk assessment tool in family medicine and obstetrics/gynecology providers but not in pediatrics (Falconi-McCahill, Lee, & Knights, 2022). The researchers theorized that based on years in practice, the pediatric providers may not have had training on sexual health, sexual orientation, or gender identity as part of medical school training.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, regular and repeated teaching on PrEP, such as the educational lecture we provided during this intervention, is needed for all clinicians because many did not have this education in their formal training. A previous study that tested an intervention to improve PrEP uptake at a FHQC found they were able to increase PrEP prescriptions using education and an electronic HIV risk assessment tool in family medicine and obstetrics/gynecology providers but not in pediatrics (Falconi-McCahill, Lee, & Knights, 2022). The researchers theorized that based on years in practice, the pediatric providers may not have had training on sexual health, sexual orientation, or gender identity as part of medical school training.…”
Section: Discussionmentioning
confidence: 99%
“…Although expanding services is inherently challenging, PrEP has been effectively introduced in primary care, sexual and gender minority healthcare settings, STI clinics, federally qualified health centers, and Health Maintenance Organization clinics; lessons learned from these initiatives provide guidance for a similar expansion of services in methadone clinics. 22,34 For example, the "no wrong doors" model that has been used to improve access and initiation of complementary services. The no wrong doors model is predicated on establishing a hub of complementary services for patients on the edge of care.…”
Section: Discussionmentioning
confidence: 99%